Education and productivity in times pandemic: discourses and senses in digital media - Silveira Galli, Fernanda Correa [UNESP]; Biziak, Jacob dos Santos (Rg Editora, Univ Estadual Campinas-unicamp, 2021)
In times of social isolation caused by the coronavirus crisis (COVID-19), approaches to remote teaching have been the subject of heated discussions, both on the part of school institutions and on the part of parents/guardians. Anchored in the theoretical-methodological framework of Discourse Analysis of a pecheuxtiana perspective, we propose a reflection on how the digital media has been discursivized education and its relationship with productivity, to understand the way these discourses work and the naturalization of a memory that returns and resignifies itself.
Keywords: Discourses; Education; Productivity; Pandemic; Digital Media